Peran Orang Tua dan Peran Teman Sebaya pada Perilaku Seksual Remaja - Adelse Prima Mulya; Mamat Lukman; Desy Indra Yani (Faletehan Health Journal, 2021)
Adolescent sexual behavior is increasingly found in everyday life. This behavior can be influenced by peers and the lack of parental role in supervising adolescents. The purpose of this study was to examine the relationship between the role of parents and peers in adolescent sexual behavior. This research was quantitative with a cross sectional study design. The study population was all tenth and eleventh graders of a senior high school in Bandung City, totaling 580 students. The samples were taken by using absolute precision estimation formula, and the sample size was 246 students. The data were collected by using a questionnaire of adolescent sexual behavior, parents role and peers role. All questionnaires had been tested for the reliability and validity. The data were analyzed by using chi Square. The results of this study showed that 49.6% of students had a high-risk sexual behavior, 53.3% had parents who played a bad role in adolescent sexual behavior, 55.7% had peers playing a major role in their sexual behavior. There was a significant relationship between the role of parents and adolescent sexual behavior; nevertheles, there was no significant relationship between the role of peers and adolescent sexual behavior. Schools were suggested to form peer groups and use millennial approaches to change adolescent behavior.